Monat der Fotografie : Wazzup ? (Wien : Fotogalerie Wien, 2006)
Bastendorff, Elvire ; Bendikov, Boris ; Bernard-Reymond, Mathieu ; Bettencourt, Gerson ; Cerevka, Radovan ; Debanne, Vincent ; Denker, Martin ; Dick, Nina ; Ewen, Luc ; Fedele di Catrano, Marco ; Gronskiy, Aleksandr ; Homola, Peter ; Joukov, Petr ; Kálinová, Andrea ; Kapralová, Daniela ; Keller, Christoph ; Kloss, Ole ; Knes, Heinz Peter ; Kolber, Véronique ; Kraus, Kitty ; Lazzarini, Francesca ; Lecomte, Tatiana ; Leimdorfer, Gilles ; Maiofis, Gregory ; Manfredi, Anja ; Mazzoni, Riccardo ; Stoyanov, Kamen ; Mishukov, Vladimir ; Munda, Philippe ; Nostri, Luca ; Nowak, Rita ; Ondzik, Jozef ; Panibratchenko, Andreï ; Parschikov, Timofey ; Passeri, Claudia ; Pervov, Georgy ; PH.ON ; Pietroniro, Giuseppe ; Rusch, Corinne ; Sarkisyan, Tatevik ; Sassi, Corrado ; Schmidt, Thyra ; Senatore, Marinella ; Serenari, Silvia ; Springer, Nina ; Strömberg, Henrik ; Szemzö, Viktor ; Tromblay, Eve K. ; Varga, Julia ; Vesely, Martin ; Vinokurova, Ira ; Weisgerber, Vera
Duits
Exhibition. Monat der Fotografie : Wazzup ?. Fotogalerie Wien, 14.11.2006 - 13.12.2006.
boek
Keywords: Berlijn; Bratislava; Luxemburg; Moskou; Parijs; Rome; Wenen